2007
DOI: 10.1038/ncpneuro0634
|View full text |Cite
|
Sign up to set email alerts
|

Surgery Insight: the role of surgery in the management of low-grade gliomas

Abstract: The benefits of surgery for the management of low-grade gliomas have been difficult to determine from the literature. This difficulty might be explained by the inconsistency of the published data, and also by advances in both neuroimaging and neurosurgical techniques, which have made surgical intervention a safer and more viable option than it has been in the past, making the earlier studies less applicable to modern care. In this article, we critically analyze the utility of surgery in the management of low-g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
59
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(62 citation statements)
references
References 73 publications
3
59
0
Order By: Relevance
“…Extent of surgical resection, timing for adjuvant radiotherapy and indication of chemotherapy for hemispheric LGG are aspects of clinical management, which remain controversial. Small study size, heterogeneity of inclusion criteria, distinct demographic series and different histological types of tumor were some of the confounding parameters preventing a consensus on the optimal therapeutic approach in this patient group 4,13,16 . A retrospective review of 216 patients with hemispheric LGG, including volumetric analysis of the extent of surgical resection, has shown that patients with at least 90% resection had 5-and 8-year OS of 97 and 91%, respectively, whereas patients with less than 90% resection had 5-and 8-year OS rates of 76 and 60%, respectively 12 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Extent of surgical resection, timing for adjuvant radiotherapy and indication of chemotherapy for hemispheric LGG are aspects of clinical management, which remain controversial. Small study size, heterogeneity of inclusion criteria, distinct demographic series and different histological types of tumor were some of the confounding parameters preventing a consensus on the optimal therapeutic approach in this patient group 4,13,16 . A retrospective review of 216 patients with hemispheric LGG, including volumetric analysis of the extent of surgical resection, has shown that patients with at least 90% resection had 5-and 8-year OS of 97 and 91%, respectively, whereas patients with less than 90% resection had 5-and 8-year OS rates of 76 and 60%, respectively 12 .…”
Section: Discussionmentioning
confidence: 99%
“…removal, as patients with more extensive tumor resection had significantly longer OS 11,[14][15][16]19,20 . Our data showed a very similar KPS at diagnosis between these two groups.…”
Section: Referencesmentioning
confidence: 99%
“…There is Class 2 evidence that resectional surgery (as defined on postoperative MRI) in high-grade glioma correlates with improved prognosis [4][5][6][7][8][9]. In low-grade gliomas, the evidence is less convincing, but many authors contend that macroscopic resection does provide benefit [10][11][12]. A significant reduction in tumour burden without morbidity is the surgical aim.…”
mentioning
confidence: 99%
“…Appropriate treatment requires representative sampling of the most aggressive part of the tumour. In enhancing tumours on CT or MRI, a portion of the contrast-enhanced section is targeted, whereas in unenhancing lesions perfusion, diffusion and spectroscopy can aid objective selection.There continues to be debate regarding the role of debulking surgery for glioma [4][5][6][7][8][9][10][11][12][13][14][15]. There is Class 2 evidence that resectional surgery (as defined on postoperative MRI) in high-grade glioma correlates with improved prognosis [4][5][6][7][8][9].…”
mentioning
confidence: 99%
“…2 Whereas high-grade gliomas are virtually incurable even after optimal surgery and adjuvant chemoradiation with a reported median overall survival of 12 to 14 months, 2,3 rate of cure reaches 50% to 70% for low-grade gliomas. [4][5][6][7][8] Whereas physical rehabilitation is a cornerstone for patients suffering from traumatic 9 or cerebrovascular 10 CNS lesions and is a fundamental part of the entire therapeutic process for complete patient recovery, rehabilitation for cancer patients with CNS involvement is rarely considered and data on its use and effectiveness are limited. 11 Poor diffusion of rehabilitation in neuro-oncology is mainly due to the skepticism about its real benefit in patients with poor prognosis such as cancer patients, for whom it is difficult to ensure a "long-lasting" compliance as complex and laborious rehabilitation interventions are planned.…”
Section: Introductionmentioning
confidence: 99%